Effect of Different Weed Management Strategies on Population Changing Pattern of Pennisetum polystachion in Coconut Plantations of Sri Lanka - Senarathne, S. H. S.; Udumann, Shashi Shermila (International Coconut Community Journal, 2019)
Pennisetum polystachion is a major problematic monocotyledonous weed species and a perennial problem in intermediate zone of coconut plantations in Sri Lanka. This study was carried out to evaluate the impacts of different management systems on P. polystachion seedling emergence patterns. The tested treatments were application of glyphosate (T1), cover cropping with Pueraria phaseoloides (T2), tractor harrowing (T3), tractor slashing (T4) and tractor ploughing (T5). All the treatments were applied twice a year except T2. As T2 cover crop at the initiation of the experiment and over grown conditions were managed by harrowing once a year. Based on the reduction in weed biomass, cover cropping (T2) was the best to reduce the P. polystachion population and to reduce P. polystachion seedling emergence density in the field. Chemical weeding was the second-best method to control the P. polystachion population in the field. The effectiveness of slashing in reducing weed seedling emergence density was lower than cover cropping and chemical weeding methods. The weed seedling emergence densities were almost similar in ploughed and harrowed plots. The seed depth of emerged seedling was very high in harrowed and ploughed treatments when compared to other treatments. Results given by T3 and T5 indicates that loosening the soil creates more favorable environment for the germination of weed seeds buried in soil. Therefore, it can be argued that the elimination of weed seeds in the top 2 cm or 4 cm in the soil seed bank by any means is likely to reduce the level of weed infestation by about 60% to 95%. Results also indicated that burying rhizomes in ploughing and harrowing treatment plots at the depths below 30 - 40 cm is effective in controlling germination of this weed species. This experiment also suggested that keeping rhizomes on the soil surface without burying for durations of 5 – 15 days would produce weak plants with poor development.